2015
DOI: 10.1556/abiol.66.2015.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with polyamines alleviate the deleterious effects of diuron in maize leaves

Abstract: the effects of diuron, a photosystem ii inhibiting herbicide, on lipid peroxidation, photosynthetic pigments, soluble protein, proline contents and some antioxidant enzymes in maize leaves were studied and protective effects of polyamines against diuron toxicity were investigated. Diuron significantly increased lipid peroxidation, suggesting oxidative damage in the plants and proline content, while it decreased total chlorophyll, carotenoid and soluble protein levels in the leaves during the experiments. Pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…It had been previously reported that SA significantly enhanced the chlorophyll content in many crop plants [60,61]. Previous studies suggest the significantly positive effects of Put on leaf chlorophyll content and was helpful in preventing the degradation of chlorophyll due to abiotic stresses [62,63].…”
Section: Discussionmentioning
confidence: 94%
“…It had been previously reported that SA significantly enhanced the chlorophyll content in many crop plants [60,61]. Previous studies suggest the significantly positive effects of Put on leaf chlorophyll content and was helpful in preventing the degradation of chlorophyll due to abiotic stresses [62,63].…”
Section: Discussionmentioning
confidence: 94%
“…SA alone had greater values for chlorophyll content than P1 inoculation (T 1 ). It had been previously reported that SA and Putrescine significantly enhance the chlorophyll content in several crop plants (Zhang et al 2009;Rivas-San Vicente and Plasencia 2011;Durmuş and Bekircan 2015). The stimulatory role of PGPR on leaf chlorophyll content had been reported previously (Vafadar et al 2014;Fahad et al 2015).…”
Section: Discussionmentioning
confidence: 54%
“…Three GR transcripts were identified in rice and wheat, whereas two GR genes were found in genomes of maize and barley [ 16 ]. There has been increasingly reported that total activity of GR in maize tissues was profoundly regulated during developmental processes as well as under exposure to multitude environmental stimuli [ 60 , 61 ]. Durmuş and Bekircan [ 61 ] established that exposure to diuron (herbicide repressing the photosystem II) boosted the total activity of GR in the maize leaves.…”
Section: Resultsmentioning
confidence: 99%
“…There has been increasingly reported that total activity of GR in maize tissues was profoundly regulated during developmental processes as well as under exposure to multitude environmental stimuli [ 60 , 61 ]. Durmuş and Bekircan [ 61 ] established that exposure to diuron (herbicide repressing the photosystem II) boosted the total activity of GR in the maize leaves. In addition, pre-treatment of Z. mays plants with putrescine caused an increment in GR activity, and additionally, it counteracted the diuron-induced increase in activity of superoxide dismutase.…”
Section: Resultsmentioning
confidence: 99%